2011
DOI: 10.1002/bdm.743
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Prisoner's Dilemma: A Reinterpretation of Coombs' Re‐parameterization

Abstract: We propose a model to measure risk in a prisoner's dilemma based on Coombs' (1973) re‐parameterization of the game as an individual risk decision‐making task that chooses between a gamble of cooperation and another gamble of defection. Specifically, we propose an index, r, to represent the risk associated with cooperation relative to defection. In conjunction with Rapoport's (1967) index of cooperation (K), our formulation of risk allows us to construct games that vary in risk (as indexed by r) while controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…There are various conceptualizations of the role of risk in social dilemmas (Au et al, 2012); perhaps the most relevant to our setting is Van Assen and Snijders 2004, where risk is defined as a person's preference between a sure thing and a gamble with the same expected value. Combining prospect theory and game theory, the authors formally showed that when cooperation is in the loss domain (as in settings where one is asked not to evacuate) the likelihood of cooperation decreases with risk aversion.…”
Section: A Brief Overview Of Literature and Methodsmentioning
confidence: 99%
“…There are various conceptualizations of the role of risk in social dilemmas (Au et al, 2012); perhaps the most relevant to our setting is Van Assen and Snijders 2004, where risk is defined as a person's preference between a sure thing and a gamble with the same expected value. Combining prospect theory and game theory, the authors formally showed that when cooperation is in the loss domain (as in settings where one is asked not to evacuate) the likelihood of cooperation decreases with risk aversion.…”
Section: A Brief Overview Of Literature and Methodsmentioning
confidence: 99%
“…Especially interesting, however, is that some prior studies even specifically focused on the PDG. In this regard, Au, Lu, Leung, Yam, and Fung () found that situational variations in the risk associated with cooperation (relative to non‐cooperation) interact with individual differences in risk aversion in shaping cooperative behaviour in the PDG. More specifically, their results showed that risk‐seeking participants cooperated more in risky games, whereas risk‐averse participants cooperated more in less risky games.…”
Section: Consistency In Choice Behaviour In Mixed‐motive Gamesmentioning
confidence: 99%
“…Glöckner and Hilbig (2012) found that the effect of risk orientation on cooperation depended on environments, such that risk aversion enhanced cooperation in cooperation-friendly environments only, but not in cooperation-unfriendly environments. Au et al (2012) suggested that the inconsistency is due to the ambiguity in defining risk of cooperation and defection in PD. They developed an index of game riskiness (r) such that a PD can be constructed to be more risky or less risky to cooperate.…”
Section: Risk Orientationmentioning
confidence: 99%
“…Whether cooperation is more or less risky could also depend on whether the outcomes are framed as gains or losses (Raub & Snijders, 1997). Au et al (2012) proposed that in a PD the relative risk of the cooperation choice to that of the defection choice can be calculated as r = (R-S) / [(R−S) + (T−P)], such that the index of game riskiness (r) ranges from 0 to 1. In essence, r is an index of the variance of the cooperation choice outcomes, R and S, relative to the variance of the defection choice outcomes, T and P. A game in which the variance of cooperation outcomes is greater than the variance of defection outcomes will have an r value greater than 0.5 that the cooperation choice is said to be more risky than the defection choice.…”
Section: Game Riskinessmentioning
confidence: 99%